PEMANFAATAN LAHAN SAWAH PUSO AKIBAT ROB MELALUI BUDIDAYA IKAN NILA BERBAGAI STRAIN DI DESA PECAKARAN KECAMATAN WONOKERTO KABUPATEN PEKALONGAN - Tri Yusufi Mardiana; M. Bahrus Syakirin (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2014)
The purpose of this study was to discover the growth response of gift, larasati and sultana tilapia to fields affected by tidal flood, to discover the impact of economic value toward tilapia harvest. The study was conducted in  15 June 2012 – 13 April 2013 in fields impacted by tidal flood in Pecakaran Village Wonokerto Sub-District Pekalongan Regency. Test fishes used were seeds of gift tilapia, larasati tilapia and sultana tilapia with average length 5 - 7 cm. Seeds of gift tilapia, larasati tilapia and sultana tilapia. Stocking density for every hapa sized 100 x 100 x 100 cm was 20 seeds. Data collecte included data of water quality and growth. Water quality parameters measured  were temperature, oxygen, pH, depth, brightness and salinity which were measured every week. Data of tilapia growth was analyzed using variant analysis and to discover tilapia type which yielded the best growth tukey test was used. Data of water quality was analyzed descriptively. The result showed that unproductive fields due to tidal flood could still be used for tilapia cultivation, different test tilapia strain used had significant influence on the growth of test tilapia, larasati tilapia had the highest growth (95.61 gr/day), followed by gift tilapia (90.04 gr/day) and the lowest was sultana tilapia (46.07 gr/day), average water quality (water temperature and pH) of culture media during the study was in adequate range for the live and growth of test tilapia.